2018
DOI: 10.1111/cen.13808
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐related effects of insulin resistance, hyperandrogenism, sympathetic dysfunction and chronic inflammation in PCOS

Abstract: Sympathetic dysfunction and hyperandrogenism are significantly associated with PCOS. Chronic low-grade inflammation potentially mediates the effect of sympathetic dysfunction on hyperandrogenism and insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 53 publications
(125 reference statements)
8
72
0
3
Order By: Relevance
“…chronic inflammation plays an important role in the development of PcoS (31,32). The Tlr4/nF-κB pathway has distinct functions during the stress reaction and inflammation (33).…”
Section: Discussionmentioning
confidence: 99%
“…chronic inflammation plays an important role in the development of PcoS (31,32). The Tlr4/nF-κB pathway has distinct functions during the stress reaction and inflammation (33).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study addressed the inter-related effects of insulin resistance, hyperandrogenism, chronic inflammation and sympathetic dysfunction (evaluated by MSNA) in 49 PCOS and 23 control women; based on the findings, the authors concluded that sympathetic dysfunction and hyperandrogenism were associated with PCOS and that chronic inflammation might be the mediating factor between sympathetic function, hyperandrogenism and insulin resistance 35. However, in the present study, the surrogate marker of sympathetic activity, LF SBP , did not significantly differ between the PCOS and control women, suggesting that in our population the women with PCOS would not have increased sympathetic activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, reported that alterations in DNA methylation profiles of the peripheral blood from women with PCOS corroborate those obtained from the ovary tissue, indicating that certain alterations in DNA methylation should be inferred from the peripheral blood, which is of great significance, as this would avoid the invasive procedure of the biopsy. Remarkably, all studies examining the peripheral blood indicate that the PCOS phenotype correlates with an alteration in the DNA methylation content of genes involved in the inflammatory response, glucose and lipid metabolism and hormone signaling, which, in turn, is associated with the presence of a systemic dysfunction characterized by chronic inflammation accompanied by hyperandrogenism and insulin resistance (Shorakae et al 2018). Besides, these alterations in the DNA methylation program could be acquired during fetal development as proposed by Lambertini et al (2017).…”
Section: R32mentioning
confidence: 97%